Pengaruh Kepemimpinan, Budaya Organisasi, Dan Komunikasi Terhadap Kinerja Pegawai Kelurahan Dengan Motivasi Sebagai Variabel Moderator Se Kecamatan Wonogiri Kabupaten Wonogiri - Utomo, Agus; Laswantini, Sri (STIE AUB Surakarta)
The aim of this study is to determine the effect of leadership, organizational culture, and communication on the performance of the administrative staff motivation as a moderator variable Wonogiri Wonogiri district.Keywords: Leadership,Organizational culture,communication,motivation,official performance